Fungi Associated to Descending Necrosis on Peach Trees at Valparaiso, Zacatecas, Mexico: First Report - Muñoz-Rocha, Belén Guadalupe; Jasso de Rodríguez, Diana; Ochoa-Fuentes, Yisa María; Hernández-Pérez, Armando; Hernández-Castillo, Francisco Daniel; Velázquez-Guerrero, Jazmín Janet; Juárez-Maldonado, Antonio (Ecosistemas y Recursos Agropecuarios, 2024)
In peach orchards of Caracoles, Valparaiso, Zacatecas, a disease manifests with the main symptom of descending necrosis in branches. Currently, the causal agents of this disease are unknown, which make it difficult itsprevention and control. The objective of the research was to identify the fungi associated with descending necrosis in the branches of the peach tree, as well as the agent that could be the causal of the disease. Roots and branches of the trees were sampled. The fungal strains were identified morphologically and molecularly, and the obtained sequences were compared with sequences reported in the GenBank database using the NCBI BLAST tool. In vivo pathogenicity tests were conducted. The fungi identified as associated with descending necrosis in branches of the Diamante ecotype peach tree were: Alternaria tenuissima, Fusarium oxysporum, and F. solani. Additionally, it was confirmed that A. tenuissima could be the causal agent of the disease.